2017
DOI: 10.1108/jedt-09-2016-0064
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and practical implications for engendering project team communication effectiveness in mass housing project delivery in Ghana

Abstract: Purpose Communication ineffectiveness inherent in the unique attributes of Mass Housing Project (MHP) features is well admitted in the body of literature. However, the understanding of the extent and nature of this influence of the unique features of MHPs requires an empirical insight. The aim of this paper is to identify the communication ineffectiveness induced by the unique features and delineate the implications of the findings for mass housing practitioners and stakeholders towards engendering effective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
4
18
0
1
Order By: Relevance
“…The theoretical underpinnings of communication and information sharing in PPP project environment is a typical interaction process of multi-disciplinary and multi-national teams, multi-cultural orientations and an exploration process of solutions, decisions and sharing of technical and scientific knowledge (Cui et al, 2018;Ochieng and Price, 2010). These interactions and information sharing are prone to various communication issues and challenges that may be induced by behavioural, technical and contextual factors (Kwofie et al, 2017(Kwofie et al, , 2018Kwofie, 2015;Gorse and Emmitt, 2007). Generally, communication process, tasks performance and actions have been perceived as a social interaction activity in a social network of teams, organizations and groups.…”
Section: Theoretical Background: Understanding Communication Issues and Challenges In Construction Project Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The theoretical underpinnings of communication and information sharing in PPP project environment is a typical interaction process of multi-disciplinary and multi-national teams, multi-cultural orientations and an exploration process of solutions, decisions and sharing of technical and scientific knowledge (Cui et al, 2018;Ochieng and Price, 2010). These interactions and information sharing are prone to various communication issues and challenges that may be induced by behavioural, technical and contextual factors (Kwofie et al, 2017(Kwofie et al, , 2018Kwofie, 2015;Gorse and Emmitt, 2007). Generally, communication process, tasks performance and actions have been perceived as a social interaction activity in a social network of teams, organizations and groups.…”
Section: Theoretical Background: Understanding Communication Issues and Challenges In Construction Project Settingmentioning
confidence: 99%
“…In one of the earliest studies on communication in construction by Higgins and Jessop (1965), it was established that the main factor underlying communication difficulties is the nature of the relationships between the communicators. In recognition of the significance of effective communication to success of an organization, project team effectiveness and managerial efficiencies, several studies have advanced the argument of improvement in behavioural factors (Gorse and Emmitt, 2007), use of ICT (El-Saboni et al, 2008;Dawood et al, 2002), communication media and network (Xie et al, 2010), communication competencies (Kwofie et al, 2017;Dai et al, 2017;Xie et al, 2010) as a sure way of improving communication in construction. In spite of the plethora of literature on improving construction communication, communication problems, issues and challenges are continuously reported as being rife in construction in various procurement and management models (see Kwofie et al, 2017;Xie et al, 2000Xie et al, , 2010Thomas et al, 1998).…”
Section: Theoretical Background: Understanding Communication Issues and Challenges In Construction Project Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…En ese mismo sector, pero en diferente contexto, Patterson (2016) indica que es posible desarrollar la EC por medio de los estilos de comunicación, los comportamientos presentes en la interacción entre individuos/grupos, los canales de distribución de información, además de su intercambio/flujo y calidad. De igual manera, Kwofie et al (2017) precisan que la EC puede ser influenciada por factores como: la exactitud, la oportunidad, la baja y la sobrecarga de información, la comprensión, las barreras, la distorsión, el mantenimiento de los canales de distribución, y, finalmente, los procedimientos de diseminación.…”
Section: Factores Que Integran a La Comunicación Efectivaunclassified
“…Various research works have underscored the need to understand the communication challenges and communication performance in various procurement typologies in construction project delivery (see Emmitt and Gorse, 2003;Xie et al, 2010;Liu, 2009; 2.3 Characteristics and communication environment of non-traditional procurement typologies Non-traditional procurement models or options collectively refer to procurement routes that provide a unified interface between the construction project process and the employer's organization, enabling enhanced benefits in time, risks integrated process, and improved performance over traditional procurement models (Hartmann and Bresnen, 2011;Hughes et al, 2006;Hughes and Murdoch, 2001). Non-traditional procurement models or options are said to differ from traditional procurement options in the structure of the procedure, the allocation of responsibility, governance and liability between the employer and the contractor (Kwofie et al, 2017;Xue et al, 2010;Pryke and Pearson, 2006;Hughes et al, 2006). Hartmann and Bresnen (2011), Xue et al (2010) and Pryke and Pearson (2006) identified CW, Integrated Project Delivery (IPD), RC, Alliancing and Partnership.…”
Section: Introductionmentioning
confidence: 99%